Designing the METTAREKA interface: collaborative interaction during 15th century voyage - Tengku Siti Meriam Tengku Wook; Siti Fadzilah Mat Noor; Hazura Mohamed; Normala Rahim; Ismahafezi Ismail; Adina Quraisa Ibrahim; Intan Yusrina Zairon; Dayang Hajah Tiawa Awang Haji Hamid (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research delves into enhancing the user experience within a Metaverse environment through the development of a collaborative virtual reality interface called METTAREKA (Metaverse of Gallery REKA). Rooted in the GeSToUX model and adapted for virtual reality headset technology and collaborative interaction, METTAREKA aims to provide an immersive exploration of the 15th-century voyage in Southeast Asia. The study identifies key problems in existing virtual systems, emphasizing the need to stimulate visitors' knowledge and experience effectively. To address this, METTAREKA integrates non-touchable gesture movement techniques and collaborative aspects, allowing multiple users to interact using virtual reality headset technology. The immersive environment features avatars, digital storytelling, and collaborative navigation and editing, promoting a dynamic and interconnected digital realm where users collaboratively engage with the history and heritage presented. The study contributes to the evolving landscape of immersive technologies, fostering collaborative interactions that redefine how individuals work, socialize, and innovate within the digital sphere.